Effectiveness of Group Counseling with Behavioral Contract Technique to Enhance Vocational Students’ Work Readiness - Ratna Khairani; Alfin Siregar (MASI Mandiri Edukasi, 2025)
This study aims to examine the effectiveness of group counseling using the Behavioral Contract Technique (Group Counseling with Behavioral Contract Technique / GC-BCT) in improving the work readiness of vocational high school students. The study employs a quasi-experimental design with a pretest–posttest control group model. The research sample consists of 30 students selected purposively and divided into two groups: experimental and control, each comprising 15 students. The instrument used is the Work Readiness Scale with high reliability (Cronbach’s Alpha = 0.91). Data analysis was conducted using paired t-tests and independent t-tests with the assistance of SPSS version 25. The research results indicate that there was a significant increase in students' work readiness after participating in group counseling services using the behavioral contract technique, with a calculated t-value of 4.280 and a Sig. (2-tailed) of 0.001 (< 0.05). Improvements occurred in the aspects of discipline, responsibility, communication, and achievement motivation. These results demonstrate that GC-BCT is effective in enhancing vocational high school students' work readiness, as it promotes behavioral commitment and collective responsibility through social reinforcement within the group.